In Dogged Pursuit: A Reassessment of the Dog's Domestication and Social Incorporation - Ochoa, Janine Therese (Hukay; Vol 8 (2005), 2016)
The dog is the earliest known animal domesticate and is the most intensely studied animal outside of humans. Archaeology has provided varied evidence for its long prehistory, while other fieldsethology, genetics, paleontology, and othershave also greatly contributed to our understanding of this canid's evolution and domestication. In the Philippines and Southeast Asia, the presence of dogs is said to be associated with the onset and development of Neolithic cultures. A recent find of a dog's remains in Ille Cave , Palawan Island provides an avenue in which to study and reanalyze this fascinating animal's prehistory in this part of the world.